2011
DOI: 10.1590/s1807-59322011000400024
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with the nitric oxide synthase inhibitor, L-NAME, attenuates estradiol-mediated improvement of learning and memory in ovariectomized rats

Abstract: INTRODUCTION:The role of ovarian hormones and nitric oxide in learning and memory has been widely investigated.OBJECTIVE:The present study was carried out to evaluate the effect of the nitric oxide synthase (NOS) inhibitor, N (G)-nitro-L-arginine methyl ester (L-NAME), on the ability of estradiol to improve learning in OVX rats using the Morris water maze.METHODS:Forty rats were divided into five groups: (1) ovariectomized (OVX), (2) ovariectomized-estradiol (OVX-Est), (3) ovariectomized-L-NAME 10 (OVX-LN 10),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 67 publications
3
16
0
Order By: Relevance
“…The results also showed that the animals of the OVX Group remembered the location of platform better than sham-operated ones. These results were in agreement with the previous studies 17,19 . In contrast with these findings, Herlitz et al showed that there were no considerable differences in cognitive performance between premenopausal and postmenopausal women 23 .…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The results also showed that the animals of the OVX Group remembered the location of platform better than sham-operated ones. These results were in agreement with the previous studies 17,19 . In contrast with these findings, Herlitz et al showed that there were no considerable differences in cognitive performance between premenopausal and postmenopausal women 23 .…”
Section: Discussionsupporting
confidence: 94%
“…In contrast with these findings, Herlitz et al showed that there were no considerable differences in cognitive performance between premenopausal and postmenopausal women 23 . We have previously shown that administration of 2 mg/kg estradiol for eight weeks improved learning and memory in ovariectomized rats, but it had deleterious effect in sham-operated ones 18,19 . Therefore, the effect of chronically administering a higher dose of estradiol was examined in the present study.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations